Physical activity volume, frequency, and intensity: Associations with hypertension and obesity over 21 years in Australian women - Gregore I. Mielke; Ding Ding; Shelley E. Keating; Bruno P. Nunes; Ruth Brady; Wendy J. Brown (Elsevier, 2024)
Background: Optimal patterns of accrual of recommended levels of physical activity (PA) for prevention of hypertension and obesity are not known. The overall aim of this study was to investigate whether different patterns of accumulation of PA are differentially associated with hypertension and obesity in Australian women over 21 years. Specifically, we investigated whether, for the same weekly volume of PA, the number of sessions (frequency) and vigorousness of PA (intensity) were associated with a reduction in the occurrence of hypertension and obesity in women. Methods: Data from the 1973-1978 and 1946-1951 cohorts of the Australian Longitudinal Study on Women's Health were analyzed (n = 20,588; 12%-16% with a Bachelor's or higher degree). Self-reported PA, hypertension, height, and weight were collected using mail surveys every 3 years from 1998/2000 to 2019/2021. Generalized Estimating Equation models with a 3-year lag model were used to investigate the association of PA volume (metabolic equivalent min/week) (none; 33-499; 500-999; ≥1000, weekly frequency (none; 1-2 times; 3-4 times; 5-7 times; ≥8 times), and the proportion of vigorous PA to total volume of PA (none; 0%; 1%-33%; 34%-66%; 67%-100%) with odds of hypertension and obesity from 2000 to 2021. Results: The cumulative incidence of hypertension was 6% in the 1973-1978 and 23% in the 1946-1951 cohort; 27% of women in the 1973-1978; and 15% in the 1946-1951 cohort developed obesity over the period. Overall, a higher volume of PA was associated with reduced odds of hypertension and obesity. When the volume of PA was considered, the odds of hypertension did not vary according to the frequency or intensity of PA. However, increased proportion of vigorous PA to the total volume of PA was associated with a small additional reduction in the risk of obesity. Conclusion: PA volume appears to be more important than the pattern of accumulation for the prevention of hypertension and obesity. Incorporating more sessions, particularly of vigorous-intensity PA, may provide extra benefits for the prevention of obesity.